The Doubled-Edge Sword of Raising the Minimum Wage: The Case of Indonesia - Fitriya; Basyith, Abdul; Zainal, Rabin Ibnu (Asian Economic and Financial Review, 2020)
This study examines the impact of minimum wage on labor productivity, financial performance and foreign direct investment (FDI). The data was collected from the quarterly financial statements of listed firms from 2010 to 2018. The manufacturing sector was selected, which comprises 175 firms from 619 listed firms in 2018. The variables are salary expenditure, change in salary expenditure, productivity, financial performance, FDI and minimum wage. A random effect generalized least squares was employed and the results revealed that the minimum wage has a negative impact on labor productivity and financial performance but is not significant. The negative results indicate that an increase in minimum wage is slower than inflation rate, thus it can only cover the cost of living. Furthermore, an increase in minimum wage affects the higher cost of production thereby reducing company profits. It appears that changes in the minimum wage have a negative and significant impact on FDI in Indonesia.